The effect of copper doping on the structural properties and composition of iron oxide nanoparticles of Ulakan Pariaman Beach sand prepared by the ball milling method - Fandriani, Diny; Erwin, Erwin (Indonesian Physics Communication, 2025)
This study explores the utilization of beach sand from Ulakan Pariaman as a source of iron oxide-based magnetic material through processes of separation, refinement, and copper (Cu) doping. The samples were processed using an iron sand separator (ISS) to separate iron oxide from other oxides, followed by treatment with a neodymium iron boron (NdFeB) magnet and ball milling technique with variations in milling time and ball size Cu doping was applied to compositions of (Fe2O3)100-xCux where x = 0; 5; 10; 15; and 20 wt.%, to investigate changes in structural and magnetic properties. XRD characterization revealed the dominance of the spinel phase of magnetite (Fe3O4) and a partial transformation to maghemite (γ-Fe2O3) indicated by changes in peak width and intensity. XRF analysis confirmed a decrease in Fe content and an increase in Cu concentration, suggesting ionic substitution within the crystal lattice. Magnetic susceptibility with higher increasing Cu content, demonstrating a positive effect of doping on the material's magnetic response.